Boosting Grade I Students' Reading Skills: A School Literacy Movement Analysis: Meningkatkan Kemampuan Membaca Siswa Kelas I melalui Gerakan Literasi Sekolah: Analisis di SD Muhammadiyah 2 Tulangan - Lestari, Triwidiya; Astuti, Ruli (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to assess the impact of the School Literacy Movement program on the reading skills of grade I students at SD Muhammadiyah 2 Tulangan in Indonesia. Employing a quantitative approach, data was collected through tests and questionnaires. The sample comprised 24 grade I students. The findings revealed that the School Literacy Movement variable accounted for 73.8% of the variance in students' reading skills, while the remaining 26.2% was attributed to external variables or error. Test results indicated that over 50% of the students demonstrated excellent reading skills, with 13 students falling in the